The effect of firm subsidies on credit markets - Aleksandr Kazakov; Michael Koetter; Mirko Titze; Lena Tonzer (Halle Institute for Economic Research (IWH), 2024)
We use project-level information for the largest regional economic development program in German history to study how government subsidies to firms affect credit markets. We identify credit market responses by considering both, bank lending and firm borrowing during 1998-2019. We find that subsidies lead to larger lending volumes without crowding out credit to non-subsidized firms. Banks that are more exposed to subsidized firms exhibit moderately higher credit risk though. Firm subsidies support lending especially when credit constraints are elevated during the years of the financial crisis.
Keywords: G21; G28; H25; 330; bank stability; financial intermediation; government subsidies